1997
DOI: 10.1093/qjmed/90.2.111
|View full text |Cite
|
Sign up to set email alerts
|

Is the common 677C-->T mutation in the methylenetetrahydrofolate reductase gene a risk factor for neural tube defects? A meta-analysis

Abstract: The common 677C-->T mutation (+) in the 5,10-methylenetetrahydrofolate reductase gene, resulting in decreased activity of the enzyme, has been associated with spina bifida neural tube defects (NTD). We combined all known Dutch control groups, a total of 1273 individuals, and found a prevalence of the 677C-->T mutation of 8.4%. When compared with the frequencies in 55 SB patients and to mothers with a child with SB their parents, this gave an OR of 1.9 [95% CI 1.1-3.3] for mothers and an OR of 1.5 [95% CI 0.74-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
99
2
14

Year Published

1998
1998
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(129 citation statements)
references
References 8 publications
14
99
2
14
Order By: Relevance
“…The reduced activity of the MTHFR enzyme in individuals with the MTHFR 677TT genotype, decreases the availability of 5-methyltetrahydrofolate which plays a key role in methylation (10) and decreases global DNA methylation (63,64) ; therefore, it is no surprise that this specific mutant gene has been extensively investigated as a genetic risk factor for NTD (65,66) . Over the past two decades, several reports have shown a 2 to 4-fold increased risk of NTD if the infant or the mother has the MTHFR 677TT genotype (65,(67)(68)(69)(70) . van der Put et al (71) reported an even higher risk of an NTD pregnancy if both the mother and the fetus were homozygous for the MTHFR 677C T polymorphism.…”
Section: The Role Of the Mthfr 677c T Polymorphism In Neural Tube Defmentioning
confidence: 99%
“…The reduced activity of the MTHFR enzyme in individuals with the MTHFR 677TT genotype, decreases the availability of 5-methyltetrahydrofolate which plays a key role in methylation (10) and decreases global DNA methylation (63,64) ; therefore, it is no surprise that this specific mutant gene has been extensively investigated as a genetic risk factor for NTD (65,66) . Over the past two decades, several reports have shown a 2 to 4-fold increased risk of NTD if the infant or the mother has the MTHFR 677TT genotype (65,(67)(68)(69)(70) . van der Put et al (71) reported an even higher risk of an NTD pregnancy if both the mother and the fetus were homozygous for the MTHFR 677C T polymorphism.…”
Section: The Role Of the Mthfr 677c T Polymorphism In Neural Tube Defmentioning
confidence: 99%
“…The best-characterized MTHFR genetic polymorphism is a 677CAET transition that affects the predicted catalytic domain of the MTHFR protein. This mutation, resulting in decreased enzyme activity, is associated with mildly elevated plasma homocysteine levels and a redistribution of folates, namely, elevated red cell folate and lowered plasma folate (van der Put et al 1995(van der Put et al , 1996. Homozygosity for the 677T mutation predisposes individuals to the development of hyperhomocysteinemia, especially during times of folate insufficiency van der Put et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the two MTHFR polymorphisms (677CAET and 1298AAEC) have been widely investigated as genetic risk factors for NTDs. Although the MTHFR C677T mutation is considered a genetic risk factor for NTD by some (Kirke et al 1993;Mills et al 1995;van der Put et al 1995van der Put et al , 1996van der Put et al , 1997aWhitehead et al 1995;Ou et al 1996), there are studies that could not Abstract Homozygosity for the C677T mutation in the methylenetetrahydrofolate reductase (MTHFR) gene is a risk factor for neural tube defects (NTDs) in many populations, including Italians. Another common mutation on the MTHFR gene, A1298C, has also been described as a risk mutation.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the mutation has been shown to be a risk factor for premature cardiovascular disease 3,4 and neural tube defect. 5,6 Deficient activity of MTHFR may also be associated with psychiatric conditions such as mental retardation, schizophrenia, 7-9 and affective disorders. 10 In line with this, a recent study of Arinami et al 1 examined the C677T polymorphism for patients with schizophrenia, bipolar disorder, and depression, and found an increased frequency of homozygosity for the T677 allele among schizophrenics (odds ratio 1.9, P = 0.0006) and among patients with unipolar depression (odds ratio 2.8, P = 0.005), but not among patients with bipolar disorder (odds ratio 1.0).…”
mentioning
confidence: 99%